PENGARUH PERDAGANGAN INTERNASIONAL DAN KEBIJAKAN FISKAL TERHADAP PERTUMBUHAN EKONOMI DI KOTA MEDAN - Yohnwein, Rudy; Ruslan, Ruslan; Azmi, Syariful (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Regional economic growth is an important indicator in assessing the success of development, where international trade and fiscal policy are two strategic factors that interact in influencing the dynamics of the regional economy. Medan city, as a center of trade and logistics in western Indonesia, has a strategic position on the map of international trade, particularly through export-import activities and the movement of goods at Belawan port. On the other hand, local government fiscal policy also determines the effectiveness of development financing through public spending and local tax management. This research aims to comprehensively analyze how international trade and fiscal policy influence economic growth in Medan city, as well as to identify legal and administrative challenges that hinder the optimization of these two factors. The research method used is a normative legal approach with descriptive-analytical methods, supported by secondary data in the form of legal documents, legislation, official statistical reports, and scientific literature. The results of the research show that international trade contributes positively to the economic growth of Medan City, particularly through increased export volume, logistics connectivity, and the role of ports as regional distribution centers. However, there are still various obstacles such as unclear export-import regulations, weak law enforcement, and low coordination among related agencies. Meanwhile, regional fiscal policies show a role in promoting infrastructure development and public services, but have not been optimal due to limited fiscal capacity and high dependence on transfer funds from the central government. In conclusion, although international trade and fiscal policy have a significant influence on the economic growth of the city of Medan, reforms in trade regulations and the strengthening of regional fiscal capacity are necessary to ensure that their contributions can be maximized sustainably. This study recommends the harmonization of cross-sectoral policies, improvement of fiscal institutional quality, and simplification of export-import regulations as strategic steps towards more inclusive and equitable economic growth.Keyword: International Trade, Fiscal Policy, Economic Growth, Economic Law, Medan City.Abstrak: Pertumbuhan ekonomi daerah merupakan indikator penting dalam menilai keberhasilan pembangunan, di mana perdagangan internasional dan kebijakan fiskal menjadi dua faktor strategis yang saling berinteraksi dalam memengaruhi dinamika ekonomi regional. Kota Medan sebagai pusat perdagangan dan logistik di wilayah barat Indonesia memiliki posisi strategis dalam peta perdagangan internasional, khususnya melalui aktivitas ekspor-impor dan pergerakan barang di pelabuhan Belawan. Di sisi lain, kebijakan fiskal pemerintah daerah juga turut menentukan efektivitas pembiayaan pembangunan melalui belanja publik dan pengelolaan pajak daerah. Penelitian ini bertujuan untuk menganalisis secara menyeluruh bagaimana pengaruh perdagangan internasional dan kebijakan fiskal terhadap pertumbuhan ekonomi di Kota Medan, serta mengidentifikasi tantangan hukum dan administratif yang menghambat optimalisasi kedua faktor tersebut. Metode penelitian yang digunakan adalah pendekatan hukum normatif dengan metode deskriptif-analitis, yang didukung oleh data sekunder berupa dokumen hukum, peraturan perundang-undangan, laporan statistik resmi, dan literatur ilmiah. Hasil penelitian menunjukkan bahwa perdagangan internasional memberikan kontribusi positif terhadap pertumbuhan ekonomi Kota Medan, terutama melalui peningkatan volume ekspor, konektivitas logistik, dan peran pelabuhan sebagai pusat distribusi regional. Namun, masih terdapat berbagai hambatan seperti ketidakjelasan regulasi ekspor-impor, lemahnya penegakan hukum, dan rendahnya koordinasi antarinstansi terkait. Sementara itu, kebijakan fiskal daerah menunjukkan peran dalam mendorong pembangunan infrastruktur dan pelayanan publik, tetapi belum optimal akibat keterbatasan kapasitas fiskal serta ketergantungan tinggi terhadap dana transfer dari pemerintah pusat. Kesimpulannya, meskipun perdagangan internasional dan kebijakan fiskal memiliki pengaruh signifikan terhadap pertumbuhan ekonomi Kota Medan, diperlukan reformasi regulasi perdagangan serta penguatan kapasitas fiskal daerah agar kontribusinya dapat dimaksimalkan secara berkelanjutan. Penelitian ini merekomendasikan harmonisasi kebijakan lintas sektor, peningkatan kualitas kelembagaan fiskal, serta penyederhanaan regulasi ekspor-impor sebagai langkah strategis menuju pertumbuhan ekonomi yang lebih inklusif dan berkeadilan..Kata kunci: Perdagangan Internasional, Kebijakan Fiskal, Pertumbuhan Ekonomi, Hukum Ekonomi, Kota Medan.